OCCURRENCE OF ENTEROCIN GENES AMONG ENTEROCOCCI STRAINS ISOLATED FROM HUMAN GASTROINTESTINAL TRACT - І. Л. Гармашева (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2016)
Aim. To investigate the presence of genes of the most common enterocins А, В and Р and to compare antagonistic activity spectra and presence of enterocin genes among enterococci strains, isolated from gastrointestinal tract of elderly people. Methods. Polymerase chain reaction with primers specific to genes of enterocin А, В and Р and statistical data processing using cluster analysis. Results. Genes of enterocin А, В and Р were found in 21 from 58 (64%) enterococci strains, and in 13 strains were found two enterocin genes, and in 3 strains – genes of enterocin А, В and Р. The strains with narrow antagonistic spectrum harbored gene combinations А/В/Р, А/В, or one of the enterocin genes. The strains with wide antagonistic specrtum also harbored from 1 to 3 enterocin genes. No relation of antagonistic spectra from Enterococcus species was found. The presence of gene enterocin A, gene combinations А/В and А/В/Р was found only in E. faecium strains. Conclusions. Gene of enterocin P and gene combination А/Р were the most frequent among enterococci strains used. The spectrum of antagonistic activity does not depend on Enterococcus species and presence of enterocin genes А, В and Р.